Weird science jokes to tickle your funny bone - Niven, Felicia Lowenstein (Berkeley Heights, NJ : Enslow Publishers, 2011)
"Includes jokes, limericks, knock-knock jokes, tongue twisters, and fun facts about animals, plants, weather, outer space, recycling, and more, and describes how to create your own funny board game"--Provided by publisher.
Includes bibliographical references (p. 47) and index.
Keywords: Science -- Juvenile humor